Effects of sodium dodecylbenzene sulfonate (SDBS), active principle of detergents, on the liver and kidney of zebrafish (Danio rerio) - Reis Santos, Eduardo Libanio [UNESP]; Silva, Odaiza [UNESP]; de Oliveira-Lima, Jeffesson; Camargo-Mathias, Maria Izabel [UNESP] (Taylor & Francis, 2025)
Sodium dodecylbenzene sulfonate (SDBS), a predominant component in detergents, requires an evaluation of its toxicological potential due to its hazardous environmental levels. Therefore, we evaluated the toxicological effects of SDBS on the liver and kidney of male D. rerio. Therefore, we evaluated the toxicological effects of SDBS on the liver and kidney of male D. rerio. The fish were divided into three groups: 0.0 (control), 0.25, and 0.5 mg/L of SDBS with exposure for up to 96 hours. After exposure, histopathological, histochemical (hepatic glycogen content), and biochemical analyses (SOD and CAT enzyme analysis) were performed on both organs. The results showed significant histopathological effects, such as circulatory disturbances and progressive and regressive alterations, leading to an altered histopathological alteration index. SOD and CAT enzymes exhibited prominent changes. Thus, it became clear that the surfactant SDBS can cause serious hepatic and renal problems in D. rerio fish, even with short-term exposure, necessitating more stringent control and regulation in the disposal of this surfactant.
Keywords: Antioxidant defense; biomarkers; environmental health; histopathology; surfactant